2017
DOI: 10.1002/num.22154
|View full text |Cite
|
Sign up to set email alerts
|

Time‐splitting methods with charge conservation for the nonlinear Dirac equation

Abstract: In this work, four numerical time‐splitting methods are proposed for the (1 + 1)‐dimensional nonlinear Dirac equation. All of these methods (or schemes) are proved to satisfy the charge conservation in the discrete level. To enhance the computation efficiency, the block Thomas algorithm is adopted. Numerical experiments are given to test the accuracy order for these schemes, to simulate numerically the binary collision including two standing waves and two moving solitons, meanwhile, the dynamic properties for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The splitting methods form an important group of methods which are quite accurate and efficient [57]. Actually, they have been widely applied for dealing with highly oscillatory systems such as the Schrödinger/nonlinear Schrödinger equations [1,8,9,22,23,55,67], the Dirac/nonlinear Dirac equations [5,6,14,54], the Maxwell-Dirac system [10,49], the Zakharov system [12,13,41,50], the Gross-Pitaevskii equation for Bose-Einstein condensation (BEC) [11], the Stokes equation [21], and the Enrenfest dynamics [32], etc.…”
mentioning
confidence: 99%
“…The splitting methods form an important group of methods which are quite accurate and efficient [57]. Actually, they have been widely applied for dealing with highly oscillatory systems such as the Schrödinger/nonlinear Schrödinger equations [1,8,9,22,23,55,67], the Dirac/nonlinear Dirac equations [5,6,14,54], the Maxwell-Dirac system [10,49], the Zakharov system [12,13,41,50], the Gross-Pitaevskii equation for Bose-Einstein condensation (BEC) [11], the Stokes equation [21], and the Enrenfest dynamics [32], etc.…”
mentioning
confidence: 99%
“…Since k 0 ≫ 1, the factors exp[∓iσ 1 k 0 ∆t] dominate the evolutions of α n and β n . Accordingly, we use the standard perturbation theory approach and seek solutions of (19) in the form:…”
Section: Unconditionally Unstable "Noise Floor"mentioning
confidence: 99%
“…Given the wide popularity of the SSM for NLS-type models, it is not surprising that it was also used extensively in studying solutions of the Gross-Neveu model (2). In numerical simulations of [17,18,19], SSM's performance for this model was favorably compared to that of other methods. In recent studies [20,21], it was shown that the SSM is capable of resolving distinctly different scales, i.e., of efficiently obtaining highly-oscillatory solutions, that occur in the non-relativistic regime of (2).…”
Section: Introductionmentioning
confidence: 99%
“…The CN finite difference method and the exponential wave integrator Fourier pseudospectral method were developed by Bao et al in 2016 [16]. Besides, there are some other numerical techniques, such as multisymplectic Runge-Kutta methods [17], an efficient adaptive mesh redistribution method [18], an integrating factor method [19], and time-splitting methods with charge conservation [20]. Some experts also discussed the spin-orbitcoupled Bose-Einstein condensates [21] and the MaxwellDirac system [22][23][24] which are related to the NLD equation.…”
Section: Introductionmentioning
confidence: 99%